Nacella TERRORIS - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA TERRORIS (FILHOL, 1880) (FIG. 12) Patella terroris Filhol, 1880: 1095; Filhol, 1885: 529. Nacella ( Patinigera ) illuminata Suter, 1913: 77. Patinigera terroris – Powell, 1955: 69. Nacella ( Patinigera ) terroris – Powell, 1973: 200, pl. 182, figs 3, 4; Powell, 1979: 42, pl. 15, 16. Nacella terroris – González-Wevar et al. , 2017: 862. Material studied: Perseverance Harbour, Campbell Island (52°33’02.14’’ S, 169°09’08.38’’ E) N = 3. Shell: The shell shape and sculpture are constant in the three analysed specimens (Fig. 12A–C). The species exhibits a conical morphology, dorsally raised, with a very thick and non-translucent shell (Fig. 12A–F). The anterior part of the animal is laterally compressed (Fig. 12D–F). The shell is of medium size (maximum length 80 mm) and exhibits a high profile. The apex is situated at the anterior 40% of the shell. All the slopes are convex (Fig. 12A– C). The aperture is oval. The surface of the shell is sculptured with raised angular primary radial ribs, weaker secondary ones and concentric growth lines that are visible in the interspaces. The margin of the shell is crenulated. The external coloration is pale reddish-brown and grey. The primary and secondary ribs are red-brown to ash-coloured to dark brown with clearer interspaces. The internal part of the shell has a soft metallic-brown coloration with dark lines corresponding to external colour patterns, bordered by a white/brown halo. External anatomy: The ventral area of the foot is grey and the epipodial fringe is quite recognizable. The mantle fold is thin and dun-brown coloured. The mantle tentacles are not pigmented and in alternate series of three white and a white longer one (Fig. 12G). The cephalic tentacles are dorsally pigmented with a black line (Fig. 12G). Radula: The first lateral teeth are set close together on the anterior edge of the basal plates, long and sharp pointed, with two long cusps. The second laterals are broader, wider spaced with three short cusps (Fig. 12H). Distribution: Campbell Island, sub-Antarctic New Zealand (Fig. 12I). Habitat: Low intertidal and subtidal rocky ecosystem down to 30 m. Comments: Multi-locus phylogenetic reconstructions recognized N. terroris from Campbell Island as a distinct taxonomic unit, closely related to Macquarie Island’s N. macquariensis and to N. edgari from Kerguelen and Heard Islands. Phylogenetic relationships and divergence time estimates indicate that Nacella species from New Zealand ( N. terroris ) and Australia ( N. macquariensis ) constitute a recent offshoot from the Kerguelen Archipelago (González- Wevar et al. , 2017). MOLECULAR ANALYSES As previously demonstrated (Nakano & Ozawa, 2004, 2007; González-Wevar et al. , 2010, 2017), the monophyly of Nacellidae ( Nacella + Cellana ), as well as the molecular distinction and the sister relationship between Nacella and Cellana , were highly supported (Fig. 13). Within Nacella , no topological inconsistencies were detected when comparing mitochondrial and nuclear markers. Phylogenetic reconstructions recognized the division of Nacella into two main clades. The first (I) includes South American lineages, while the second (II), those from maritime Antarctica and sub- Antarctic islands (Fig. 13). In South America, main clade I includes individuals of the new Magellanic lineage (a) N. yaghana sp. nov. (Fig. 13). All the analysed specimens from Pía and Garibaldi Fjords, Beagle Channel, fell within a clearly resolved, reciprocal monophyletic clade and, therefore, represent a new previously unrecognized Nacella species here described (Fig. 13). Lineage (b) includes all the individuals of N. clypeater collected along Central Chile in the Pacific margin of South America between 42°S and 30°S (Fig. 13). Finally, lineage (c) represents the most diverse South American group and includes Magellanic species: N. deaurata , N. flammea , N. magellanica and N. mytilina . As observed in previous studies (González-Wevar et al. , 2010), mitochondrial DNA reconstructions recognized the reciprocal monophyly of N. mytilina and N. flammea , but failed to recover that between N. deaurata and N. magellanica . However, 28S rRNA and the concatenated analyses (Fig. 13) recovered the reciprocal monophyly of all four Magellanic species with strong support. Accordingly, the current diversity of Nacella in South America includes three lineages (a–c) and six species ( N. clypeater , N. deaurata , N. flammea , N. magellanica , N. mytilina and N. yaghana sp. nov.). The second main clade II includes Nacella species from sub-Antarctic islands and from maritime Antarctica (Fig. 13). Lineage (d) includes the species N. edgari (Kerguelen and Heard Islands), N. macquariensis (Macquarie Island) and N. terroris (Campbell Island). All the methods and molecular markers recognized N. edgari as a monophyletic unit, including individuals previously labelled N . cf. macquariensis from Heard Island (González-Wevar et al. , 2010) (Fig. 13). At the same time, the species N. macquariensis (Macquarie Island) and N. terroris (Campbell Island) are both monophyletic and form a clade closely related to N. edgari (Fig. 13). Lineage (e) includes individuals of N. kerguelenensis (Kerguelen and Heard Islands), but this species was not found at Macquarie Island as reported by Powell (1973). Interestingly, high levels of genetic divergence characterize the sympatric species N. kerguelenensis and N. edgari . In fact, molecular divergence between these sympatric species are similar to those recorded between Antarctic and sub-Antarctic lineages of the genus (González-Wevar et al. , 2012b, 2016b). Finally, lineage (f) includes the Antarctic limpet N. concinna and its sister species N. delesserti from the sub-Antarctic Marion and Crozet Islands (Fig. 13). Accordingly, the diversification of Nacella in the Kerguelen Plateau and New Zealand Islands includes two main lineages (d and e) and four species ( N. edgari , N. kerguelenensis , N. macquariensis and N. terroris ) while maritime Antarctica encompasses a single lineage (f) with two sister species ( N. concinna and N. delesserti ). : Published as part of González-Wevar, Claudio A., Hüne, Mathias, Rosenfeld, Sebastián, Nakano, Tomoyuki, Saucède, Thomas, Spencer, Hamish & Poulin, Elie, 2019, Systematic revision of Nacella (Patellogastropoda: Nacellidae) based on a complete phylogeny of the genus, with the description of a new species from the southern tip of South America, pp. 303-336 in Zoological Journal of the Linnean Society 186 on pages 325-327, DOI: 10.1093/zoolinnean/zly067, http://zenodo.org/record/5718878 : {"references": ["Filhol H. 1880. Mollusques marins vivant sur les cotes de l'ile Campbell. Comptes Rendus de l'Academie des Sciences Paris 91: 1094 - 1095.", "Filhol H. 1885. Recueil de memoires, rapports et documents relatifs a l'observation du passage de Venus sur le Soleil, Vol. III. Paris: Mission de I'le Campbell, Zoologie, Academy of Science.", "Suter H. 1913. Manual of the New Zealand Mollusca. Wellington, New Zealand: Government Printer.", "Powell AWB. 1955. Mollusca of the Southern Islands of New Zealand. Cape Expedition Series Bulletin N \u00b0 15. Wellington, New Zealand: Department of Scientific and Industrial Research.", "Powell AWB. 1973. The patellid limpets of the World (Patellidae). In: Abbot RT ed. Indo-Pacific Mollusca: monographs of the marine mollusks of the world with emphasis on those of the tropical western Pacific and Indian Oceans, Vol. 3. Auckland, New Zealand: Auckland Institute and Museum.", "Powell AWB. 1979. New Zealand Mollusca: marine, land, and freshwater shells. Auckland, New Zealand: William Collins Publishers Ltd.", "Gonzalez-Wevar CA, Hune M, Segovia NI, Nakano T, Spencer HG, Chown S, Saucede T, Johnstone G, Mansilla A, Poulin E. 2017. Following the Antarctic Circumpolar Current: patterns and processes in the biogeography of the limpet Nacella (Mollusca: Patellogastropoda) across the Southern Ocean. Journal of Biogeography 44: 861 - 874.", "Nakano T, Ozawa T. 2004. Phylogeny and historical biogeography of limpets or the order Patellogastropoda based on mitochondrial DNA sequences. Journal of Molluscan Studies 70: 31 - 41.", "Gonzalez-Wevar CA, Nakano T, Canete JI, Poulin E. 2010. Molecular phylogeny and historical biogeography of Nacella (Patellogastropoda: Nacellidae) in the Southern Ocean. Molecular Phylogenetics and Evolution 56: 115 - 124.", "Gonzalez-Wevar CA, Diaz A, Gerard K, Canete JI, Poulin E. 2012 b. Divergence time estimations and contrasting patterns of genetic diversity between Antarctic and southern South America benthic invertebrates. Revista Chilena De Historia Natural 85: 445 - 456.", "Gonzalez-Wevar CA, Hune M, Rosenfeld S, Saucede T, Feral J-P, Mansilla A, Poulin E. 2016 b. Patterns of genetic diversity and structure in Antarctic and sub-Antarctic Nacella (Patellogastropoda: Nacellidae) species. Biodiversity 17: 46 - 55."]}